Constituição do sujeito na era do capitalismo de vigilância: uma interface a partir dos estudos em ciência, tecnologia e sociedade - Melo, Samuel Cerqueira (Universidade Federal de São Carlos, 2025)
From the perspective of Science, Technology and Society (STS) studies, this work will analyse the implications of surveillance capitalism in the structuring of the digital ecosystem and in the foundation of the social architecture of the 21st Century, as well as reflecting on how these processes influence the constitution of the contemporary subject. In this context, the key role of big tech companies and their thinking machines stands out, consisting of technologies such as big data, employed to collect, extract and analyse data, which will subsequently feed artificial intelligence (AI) systems capable of shaping both individual and collective decisions. The rising dispute over sovereignty in Science and Technology (S&T) among the United States, China, and the European Union highlights different models of regulation and governance regarding the deliberate use of data, outlining diverse scenarios of control, surveillance, and sales. As a methodological approach, an inductive literature review was applied, drawing on concepts that expand the scope of view, allowing us to perceive what often remains invisible in the face of ambiguous realities. The cosmovision adopted here serves as a tool for understanding the ground we walk on with greater accuracy, especially in the face of fast economic progress. It therefore concludes with insights that focus on the subjective and emancipatory formation of the political agent, promoting the awakening of the cognizant subject to an understanding of the effects of surveillance capitalism, which tends to manipulate and subjugate human behaviour, converting personal data into economic surplus and consolidating new forms of servitude.
Constitution of the subject in the era of surveillance capitalism: an Interface from science, technology, and society studies
Keywords: Capitalismo de vigilância; Ciência, tecnologia e sociedade; Constituição do sujeito; Ecossistema digital; Inteligência artificial; Surveillance capitalism; Science, technology, and society; Constitution of the subject; Digital ecosystem; Artificial intelligence; CIENCIAS HUMANAS